Delayed sleep phase syndrome: the sleep disorder that’s out of sync - Lourdes, Asha; Chary, Kooroju Yeshwanth (International Journal Of Community Medicine And Public Health, 2025)
Delayed sleep phase syndrome (DSPS) is a chronic sleep disorder marked by a persistent delay in the sleep-wake cycle, causing individuals to fall asleep and wake up much later than desired. It affects people of all ages but is especially common in teenagers and young adults. DSPS significantly disrupts daily functioning, leading to mood swings, cognitive impairment, daytime sleepiness, and social or occupational difficulties. The disorder’s pathophysiology is complex, involving circadian rhythm misalignment, melatonin secretion irregularities, and sleep-wake imbalances. Genetic predisposition, environmental influences, and lifestyle choices can increase susceptibility and perpetuate the condition. Clinically, DSPS is characterized by late sleep onset, late rising, and a strong preference for a delayed sleep schedule. Associated traits include erratic melatonin levels, inconsistent sleep patterns, and circadian rhythm disturbances. Diagnosis requires a thorough clinical evaluation, including sleep diaries, actigraphy, polysomnography (PSG), and a detailed history. Differentiating DSPS from conditions such as insomnia, narcolepsy, or sleep apnoea is essential to avoid mismanagement. Treatment typically combines behavioral, environmental, and pharmacological strategies. Behavioral approaches include consistent sleep routines, relaxation methods, and cognitive behavioral therapy. Environmental interventions involve light therapy, sleep hygiene improvements, and melatonin supplementation. Pharmacological options may include melatonin receptor agonists, sleep-promoting agents, or wakefulness-enhancing medications. Early recognition and treatment are vital to preventing long-term impairment and improving quality of life. Raising awareness among patients, families, and healthcare professionals is crucial. This study emphasizes bridging clinical practice and research, while providing a valuable resource for students, clinicians, and investigators in sleep medicine.